Artificial intelligence : 18th Russian Conference, RCAI 2020, Moscow, Russia, October 10-16, 2020, Proceedings.: 18th Russian Conference, RCAI 2020, Moscow, Russia, October 10-16, 2020, Proceedings. ([2020]) - Unknown
No abstract available